Conjugates of methylated cyclodextrin derivatives and hydroxyethyl starch (HES): Synthesis, cytotoxicity and inclusion of anaesthetic actives - Markenstein, Lisa; Appelt-Menzel, Antje; Metzger, Marco; Wenz, Gerhard (Beilstein Journal of Organic Chemistry, 2014)
The mono-6-deoxy-6-azides of 2,6-di-O-methyl-β-cyclodextrin (DIMEB) and randomly methylated-β-cyclodextrin (RAMEB) were conjugated to propargylated hydroxyethyl starch (HES) by Cu+-catalysed [2 + 3] cycloaddition. The resulting water soluble polymers showed lower critical solution temperatures (LCST) at 52.5 °C (DIMEB-HES) and 84.5 °C (RAMEB-HES), respectively. LCST phase separations could be completely avoided by the introduction of a small amount of carboxylate groups at the HES backbone. The methylated CDs conjugated to the HES backbone exhibited significantly lower cytotoxicities than the corresponding monomeric CD derivatives. Since the binding potentials of these CD conjugates were very high, they are promising candidates for new oral dosage forms of anaesthetic actives.
Keywords: anaesthetics; complexation; cyclodextrin; LCST; lower critical solution temperature; midazolam; occupancy; polymer; sevoflurane; solubility; starch